Hypoglycemia and Glucagon Utilization in Insulin-Treated Diabetic Patients - Vilovic, Marino; Kurir, Tina Ticinovic; Novak, Anela; Krnic, Mladen; Borovac, Josip Andelo; Lizatovic, Ivan-Kresimir; Kokic, Visnja; Bozic, Josko (Experimental and Clinical Endocrinology & Diabetes, 2018)
Background First choice of therapy for severe hypoglycemia outside hospital environment is glucagon injection, an undertaught and underused remedy. Aim of this study was to investigate knowledge about glucagon therapy, possession rate and usage rate in insulin-treated diabetic patients, with special emphasis on history of hypoglycemia and severe hypoglycemia episodes.Methods In this cross-sectional study, 300 insulin-treated diabetic patients (146 males and 154 females, mean age 61.1±16.4 years) were recruited from comprehensive Diabetes Center in Croatia. Specialized self-administered, 13-item questionnaire regarding glucagon therapy and history of hypoglycemia was obtained from each patient, as well as data collected from medical history documentation.Results Experience of hypoglycemic episode was reported by 233 (77.7%), and severe hypoglycemia by 73 (24.3%) patients. Participants with experience of hypoglycemia have significantly longer diabetes duration (17.2±11.2 vs. 11.9±8.5 years, P<0.001) and lower BMI values (26.38±3.97 vs. 31.11±7.17 kg/m2, P<0.001). Knowledge about glucagon therapy had 55.3% patients, 44.7% obtained it from the pharmacy, while glucagon was used in 35.6% cases of severe hypoglycemia. Glucagon knowledge was better in patients that attended at least one diabetes lecture (P=0.038), while educational level showed no statistical significance (P=0.286). Main significant positive predictor of glucagon knowledge was history of severe hypoglycemia (OR 4.71, 95% CI 1.38 – 16.02, P=0.013).Conclusions Glucagon therapy was underused in treating severe hypoglycemia. It is highly important to emphasize value of quality education as one of the fundamentals of good diabetes management.
Keywords: hypoglycemia treatment; education; diabetes mellitus